Macrophage-Related SPP1 as a Potential Biomarker for Early Lymph Node Metastasis in Lung Adenocarcinoma - Dong, Bo; Wu, Chunli; Huang, Lan; Qi, Yu (Frontiers in Cell and Developmental Biology, 2021)
Lymph node metastasis is a major factor that affects prognosis in patients with lung adenocarcinoma (LUAD). In some cases, lymph node metastasis has already occurred when the primary tumors are still small, however, relevant studies on early lymph node metastasis are limited, and effective biomarkers remain lacking. In this study, transcriptome sequencing was performed on tissues from 16 matched patients with Stage-T1 LUAD (eight cases of lymph node metastasis and eight cases of non-metastasis), and the transcriptome profiles of Stage-T1 LUAD patients in TCGA, GSE68465, and GSE43580 cohorts were used for external verification. We identified a higher abundance of M0 macrophages in the metastatic group using the CIBERSORT algorithm and immunohistochemistry (IHC) analysis and the enrichment of the epithelial–mesenchymal transition (EMT) pathway was identified in patients with higher M0 infiltration levels. Subsequently, the EMT hallmark gene SPP1, encoding secreted phosphoprotein 1 (SPP1), was determined to be significantly correlated with macrophage infiltration and M2 polarization. In addition, SPP1 was validated as a risk indicator of early lymph node metastasis by quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) and IHC assays, and SPP1 in the blood, as detected by enzyme-linked immunosorbent assay (ELISA) showed a superior predictive capability for early lymph node metastasis (area under the curve [AUC] = 0.74). Furthermore, a potential long noncoding RNA (lncRNA, AC037441)/SPP1/macrophage correlation network was identified as involved in the regulation of lymph node metastasis using the weighted gene co-expression network analysis (WGCNA) algorithm. In conclusion, we revealed the potential role of macrophages in lymph node metastasis and identified the macrophage-related gene SPP1 as a potential biomarker for early lymph node metastasis in LUAD.